فعالية المعلمين في تحسين طرق التدريس لتعليم اللغة العربية في جامعة جنوب شرق سريلانكا: دراسة وصفية تحليلية: Teachers’ Efficacy in Improving Teaching Methods for Teaching Arabic at the South Eastern University of Sri Lanka: An analytical descriptive study - Man, Saupi; Abdul Azeez, Fathima Sabrina (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
مع تسارع التقدم العلمي، خاصة مع ظهور التكنولوجيا الحديثة، يجب على المعلمين ابتكار طرق تدريس جديدة بشكل متزايد لمواكبة متطلبات الحياة المعاصرة والتقدم الفكري للطلاب. وهي من أهم ركائز التعليم والتعلم. تتطور عملية التدريس والتعلم في مختلف المجالات العلمية، مثل العلوم الإنسانية والاجتماعية، بمرور الوقت. ولكن الدراسات السابقة تشير إلى أن هناك قصورا في توظيف طرق التدريس لتعليم اللغة العربية في سريلانكا. فهذا البحث يهدف إلى الكشف عن فعالية المعلمين في تحسين طرق التدريس لترقية مستوى طلبة جامعة جنوب شرق سريلانكا. ولتحقيق الهدف المنشود، تعتمد هذه الدراسة على المنهج الوصفي التحليلي مع استخدام الاستبانة المغلقة لدى الطلبة والأساتذة، ثم يتم تحليل البيانات باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS. وأخيرا تؤكد النتائج أن المعلمين يوظفون طريقة الأسئلة وطريقة الترجمة وطريقة القراءة وطريقة المحاضرة بدرجة عالية في تدريس اللغة العربية في جامعة جنوب شرق سريلانكا. With the acceleration of scientific progress, especially with the advent of modern technology, teachers must increasingly innovate new teaching methods to keep pace with the demands of contemporary life and the intellectual progress of students. It is one of the most important pillars of teaching and learning. Teaching and learning in various scientific fields, such as the humanities and social sciences, evolve over time. However, previous studies indicate that there is a deficiency in employing teaching methods to teach Arabic in Sri Lanka. Hence, this research aims to assess the effectiveness of teachers in improving teaching methods to upgrade the level of students at the South Eastern University of Sri Lanka. To achieve the desired goal, this study relies on the analytical descriptive approach with the use of a closed questionnaire for students and teachers, then the data is analyzed using the SPSS software. Finally, the results reveal that teachers employ the method of questions, the method of translation, the method of reading, and the method of lecture to a high degree in teaching Arabic at the South Eastern University of Sri Lanka.